2013
DOI: 10.1111/ijd.12199
|View full text |Cite
|
Sign up to set email alerts
|

A novel therapeutic strategy for turban tumor: scalp excision and combined reconstruction with artificial dermis and split skin graft

Abstract: Treatment of turban tumor is a challenge considering the localization and extensiveness of the tumor masses. This novel therapy for turban tumor leads to a very good cosmetic and functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Due to the very disfiguring nature of these head and neck, facial tumors, surgical removal and often repeated surgeries are performed on these individuals to limit tumor growth over their life-time. The psychological impacts due to the disfiguring appearance of affected individuals may lead to depression and social withdrawal [16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the very disfiguring nature of these head and neck, facial tumors, surgical removal and often repeated surgeries are performed on these individuals to limit tumor growth over their life-time. The psychological impacts due to the disfiguring appearance of affected individuals may lead to depression and social withdrawal [16].…”
Section: Introductionmentioning
confidence: 99%
“…We performed the first review of the literature about studies that describe dermal substitutes’ utilisation in reconstruction after skin tumour excision. Table enlists publications available until July 2017 …”
Section: Discussionmentioning
confidence: 99%
“…Of them, 25 did not report data about recurrence or did not provide the complete text in English in order to evaluate this aspect . Eleven studies showed no recurrences among their patients, while 6 articles reported cases of recurrence that ranged from 5% to 25% …”
Section: Discussionmentioning
confidence: 99%
“…13 Total scalp excision followed by combined reconstruction with artificial dermis and split skin graft has been used in turban tumor cases, with good results. 10,14 Topical formulations containing salicylic acid or prostaglandin A1, which act by inhibiting NF-kB, are a possible nonablative treatment for solitary or small sized lesions. 4,14,15 …”
Section: 3810mentioning
confidence: 99%
“…10,14 Topical formulations containing salicylic acid or prostaglandin A1, which act by inhibiting NF-kB, are a possible nonablative treatment for solitary or small sized lesions. 4,14,15 …”
Section: 3810mentioning
confidence: 99%